Right Sided Diaphragmatic Mesothelial Cyst in a 40 Year Old Adult Male: A Rare Congenital Anomaly - Ahmed, Hajrah Hilal; Jamaluddin, Muhammad; Irshad, Kanwal (Journal of Society of Surgeons of Nepal, 2022)
Mesothelial growths are lined by a solitary layer of mesothelial cells, and they are benign in nature. These lesions are uncommon and can be found on, or adjacent to serous membrane. Intrathoracic mesothelial growths are congenital deformities and an intradiaphragmatic site is exceptionally rare. Complete excision is obligatory for definite diagnosis. We are reporting a case of intradiaphragmatic mesothelial cyst in a 42-year-old male patient. who came with backache, shortness of breath and right sided chest discomfort. Careful extraction of the cyst was performed. The final diagnosis based on histopathology report was mesothelial cyst arising from the diaphragm.